Engineered hyporheic zones: Design and applications in stream health restoration - a review - Tewari, Ankit; Singh, Prabhat Kumar; Gaur, Shishir (IWA Publishing, 2022)
Anthropogenic deterioration of streams and rivers has affected their surface-subsurface linkages. This has led to the degradation of hyporheic zones, a sensitive interface between a stream channel and its surrounding sediments, responsible for transforming pollutants, natural solutes and supporting benthic communities. Several authors have reported the influence of stream restoration measures on hyporheic exchanges and have called for the inclusion of hyporheic zone restorations in stream management. Engineered Hyporheic Zones (EHZ) are the creation of artificial transition areas due to induced hyporheic flows, brought about by some feature modifications done to the stream channel or its subsurface. These feature modifications and their implications have been investigated through lab experiments, outdoor flumes, modelling and field studies for several years. This paper attempts to summarize the endeavours made in the study of EHZ and its applications in water quality improvement and habitat restoration. A comprehensive review of up-to-date literature with specific focus on the influence of engineered structures on hyporheic exchanges is presented, followed by the comparison of preferences opted for different studies and their limitations. The paper ends with suggestive future scope in EHZ studies and its potential as a low cost alternative treatment technology for river restoration.
This paper is submitted by the author of IIT (BHU), Varanasi , India
Keywords: Engineered hyporheic zone; Hyporheic exchange flows; Hyporheic zone; Urban stream management; Stream health restoration